Perturbation theory and renormalization group equations - Litim, Daniel F.; Pawlowski, Jan M. (Physical review. D, Particles, fields, gravitation, and cosmology, 2002)
We discuss the perturbative expansion of several one loop improved renormalization group equations. It is shown that in general the integrated renormalization group flows fail to reproduce perturbation theory beyond one loop.